Electronic Communication and Supply Chain Performance of Large Retail Chains in Kenya - Mauki, Reuben Mwenda; Odari, Sammy; Ndeto, Charles (International Journal of Supply Chain and Logistics, 2025)
Purpose: This study sought to establish the relationship between electronic communication and supply chain performance in Large Retail Chains in Kenya. The study was guided by disruptive innovation theory. Methodology: The study adopted descriptive research design and positivist research paradigm. The study targeted 12 Large Retail Chains in Kenya. The target population for this study was 240 respondents. Census method was used in this study. The study used research questionnaires to collect primary data. Qualitative data was analyzed using content analysis and presented in prose form. Qualitative data was analyzed using descriptive and inferential analysis. Descriptive statistics such as frequency, percentages, and means were used. Pearson correlation coefficient was used for testing strength and direction between the independent and the dependent variables. A multiple regression model was used to test the significance of the relationship between the independent variables and the dependent variable. Findings: The study findings revealed that electronic communication has a positive and significant effect on supply chain performance of Large Retail Chains in Kenya. The study concludes that electronic communication has a positive and significant effect on supply chain performance of Large Retail Chains in Kenya. Unique Contribution to Theory, Policy, and Practice: Based on the findings, this study recommends that the management of large retail chains in Kenya should implement integrated Electronic Data Interchange (EDI) systems to enhance communication across their supply chains. The study contributes to theory by showing electronic communication as a strategic resource for supply chain performance, informs policy by highlighting the need for supportive frameworks to enhance digital integration, and guides practice by urging retail managers to adopt EDI systems for greater efficiency and competitiveness.